Time-Course of the Innate Immune Response of the Terrestrial Crustacean Porcellio scaber After Injection of a Single Dose of Lipopolysaccharide - Dolar, Andraž; Jemec Kokalj, Anita; Drobne, Damjana (Frontiers in Immunology, 2022)
Invertebrates, including crustaceans, rely on cellular and humoral immune responses to protect against extrinsic and intrinsic factors that threaten their integrity. Recently, different immune parameters have been increasingly used as biomarkers of effects of pollutants and environmental change. Here, we describe the dynamics of the innate immune response of the terrestrial crustacean Porcellio scaber to injection of a single dose of lipopolysaccharide (LPS), an important molecular surface component of the outer membrane of Gram-negative bacteria. The aim was to provide a basis for interpretation of change in immune parameters as a result of different challenges, including microplastics and nanoplastics exposure. Changes in total and differential numbers of hemocytes, hemocyte viability, and humoral immune parameters (i.e., phenoloxidase-like activity, nitric oxide levels) were assessed at different times (3, 6, 12, 24, 48 h). An injection of 0.5 μg/μL LPS into the body of P. scaber resulted in a rapid decrease (3 h after LPS injection) in the total number of hemocytes and reduced viability of the hemocytes. This was accompanied by changed proportions of the different hemocyte types, as a decrease in the numbers of semigranulocytes and granulocytes, and a marked increase in the numbers of hyalinocytes. In addition, phenoloxidase-like activity and nitric oxide levels in the hemolymph were increased at 3 h and 6 h, respectively, after the LPS challenge. Forty-eight hours after LPS injection, the immune parameters in the hemolymph of P. scaber had returned to those before the LPS challenge. This suggests that the innate immune system successfully protected P. scaber from the deleterious effects of the LPS challenge. These data indicate the need to consider the dynamics of innate immune responses of P. scaber when effects of infections, pollutants, or environmental changes are studied. We also propose an approach to test the immunocompetence of organisms after different challenges in ecotoxicity studies, based on the dynamics of their immune responses.